PEMETAAN DAMPAK BENCANA BANJIR BANDANG PADA DAS ANAI : STUDI KASUS KECAMATAN X KOTO DAN PADANG PANJANG BARAT - Fitria Rahmi Mardhatillah; Triyatno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objectives of this research are: 1) Flash flood hazard mapping, 2) Analysis of infrastructure and land use affected by flash floods. This type of research uses Quantitative descriptive method. The results of the research are: 1) The hazard classification results are divided into 4 classes with an area of very high (240.18 Ha), high (207.22 Ha), low (325.95 Ha), and very low (425.86 Ha) from a total buffer area of 1,199.21 Ha, 2) The results of infrastructure identification affected by flash floods were 273 units out of 1,637, consisting of 233 buildings out of 1,484 buildings, 18 bridges out of 27 bridges, and 22 roads out of 126 roads. Meanwhile, in terms of land use, 702 households were affected, consisting of 396 households in agricultural land ownership, 243 households in ownership of built-up land, and 63 households in ownership of other uses. The land use identified in the buffer area is 427.97 hectares, consisting of 351.09 hectares of agricultural land, 65.04 hectares of built-up land, and 11.84 hectares of other uses. It can be concluded based on the calculation area of the results of the very high and high classification of flash flood hazards, the area of land use affected is 154.05 Ha, consisting of 128.06 Ha of agricultural land, 16.65 Ha of built-up land, and 9.34 Ha of other uses.